(8/27)^-1/3×(25/4)^1/2×(4/9)^0+(125/64)^1/3​

Question

(8/27)^-1/3×(25/4)^1/2×(4/9)^0+(125/64)^1/3​

in progress 0
Eliza 2 weeks 2021-09-06T04:25:28+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-09-06T04:26:47+00:00

    Answer:

    5

    Step-by-step explanation:

    = (8/27)^-1/3*(25/4)^1/2*(4/3)^0+(125/64)^1/3

    = (27/8)^1/3*{(5/2)^2}^1/2*1+{(5/4)^3}^1/3

    = (3/2)^3*1/3*(5/2)^2*1/2+(5/4)^3*1/3

    = 3/2*5/2+5/4

    = 15/4+5/4

    = 20/4

    = 5 answer

    I hope it is useful for you so plz mark me as brainliests and give thanks

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )